2008
DOI: 10.1680/geot.2008.58.6.471
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and macro-mechanical behaviour of DEM crushable materials

Abstract: This paper provides a micro-mechanical commentary on the macroscopic behaviour observed in DEM simulations of the compression of individual crushable grains, and of triaxial tests on assemblies of both crushable and uncrushable grains. A fragmentation ratio is defined to describe the bond breakage processes, and the significance of other micro-mechanical parameters such as sliding contacts ratio, average coordination number, deviator fabric, and internal energies per unit volume is discussed. Three different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
96
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(114 citation statements)
references
References 27 publications
8
96
0
1
Order By: Relevance
“…Cheng et al (2004) and Bolton et al (2008) quantify energy dissipation in their simulations of agglomerate crushing and use continuum Cam Clay models in their interpretation of the discrete data. Wang & Yan (2012) and Zhou et al (2013) also consider energy in their simulations of crushable agglomerates.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al (2004) and Bolton et al (2008) quantify energy dissipation in their simulations of agglomerate crushing and use continuum Cam Clay models in their interpretation of the discrete data. Wang & Yan (2012) and Zhou et al (2013) also consider energy in their simulations of crushable agglomerates.…”
Section: Introductionmentioning
confidence: 99%
“…McDowell et al (2006) used the discrete element method to model largescale triaxial experiments of ballast aggregates reinforced with geogrids, and concluded that the DEM approach holds much promise as a tool for investigating granular aggregate assemblies. Bolton et al (2008) used the DEM to simulate triaxial compression shearing tests for both breakable and unbreakable agglomerate assemblies, capturing the influence of confining pressure on the stress-strain and volumetric response. Lu and McDowell (2008) studied the stress-strain response of ballast subjected to monotonic loading using the DEM.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the fragmentation of particles under controlled conditions is used in comminution processes such as the milling of vegetal products or grinding of mineral materials. The evolution of particle size distribution and energy dissipation in such processes depend on many factors such as particle properties (shape, crushability), initial size distribution, loading history, and mobility of the grains during the crushing process [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Such aggregates may represent real aggregates such as pellets and ceramic compacts or simply be regarded as a toy model for particle fracture. This bonded particle model (BPM) has been employed to investigate the behavior of crushable soils, rocks, fault gouge, and other materials [7,22,[32][33][34][35][36][37][38][39][40][41]. An alternative method consists in replacing a circular or spherical particle at its fracture threshold by several smaller fragments of the same shape [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%